Validation and extension of the reward-mountain model - Breton, Yannick-André; Mullett, Ada; Conover, Kent; Shizgal, Peter (Frontiers in Behavioral Neuroscience, 2013)
The reward-mountain model relates the vigor of reward seeking to the strength and cost of reward. Application of this model provides information about the stage of processing at which manipulations such as drug administration, lesions, deprivation states, and optogenetic interventions act to alter reward seeking. The model has been updated by incorporation of new information about frequency following in the directly stimulated neurons responsible for brain stimulation reward and about the function that maps objective opportunity costs into subjective ones. The behavioral methods for applying the model have been updated and improved as well. To assess the impact of these changes, two related predictions of the model that were supported by earlier work have been retested: 1) altering the duration of rewarding brain stimulation should change the pulse frequency required to produce a reward of half-maximal intensity, and 2) this manipulation should not change the opportunity cost at which half-maximal performance is directed at earning a maximally intense reward. Prediction 1 was supported in all six subjects, but prediction 2 was supported in only three. The latter finding is interpreted to reflect recruitment, at some stimulation sites, of a heterogeneous reward substrate comprising dual, parallel circuits that integrate the stimulation-induced neural signals.